2006
DOI: 10.1002/glia.20418
|View full text |Cite
|
Sign up to set email alerts
|

The TLR3 ligand polyI:C downregulates connexin 43 expression and function in astrocytes by a mechanism involving the NF‐κB and PI3 kinase pathways

Abstract: Toll-like receptor 3 (TLR3) is a component of the innate immune response that responds to dsRNA viruses and virus replication intermediates. In this study we show that activation of astrocytes with the dsRNA mimetic polyinosinic-cytidylic acid (pI:C) results in loss of expression of connexin43 (Cx43) mRNA and protein while upregulating the expression of the ionotropic P2 receptor P2X(4)R. Analysis of the signaling pathways involved failed to demonstrate a role for the p38 MAP kinase, ERK, or JNK signaling path… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
36
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(40 citation statements)
references
References 48 publications
3
36
0
1
Order By: Relevance
“…38), one of which is the phosphorylation site at Ser-386. IRF3 Ser-386 phosphorylation is mediated by PI3K in response to virus infection (39). In our study, IFN-␥ induces IRF3 Ser-386 phosphorylation in a PI3K-and HDAC3-dependent manner.…”
Section: Discussionsupporting
confidence: 57%
“…38), one of which is the phosphorylation site at Ser-386. IRF3 Ser-386 phosphorylation is mediated by PI3K in response to virus infection (39). In our study, IFN-␥ induces IRF3 Ser-386 phosphorylation in a PI3K-and HDAC3-dependent manner.…”
Section: Discussionsupporting
confidence: 57%
“…Inhibition of NFB with SC514 completely abolished the increase in Cx43 expression. Several previous papers described the presence of an NFB-binding site in the promoter region of the Cx43 gene (39,40). However, the functional role of this site has not been firmly established.…”
Section: Discussionmentioning
confidence: 99%
“…''Fast'' P2X 1 and P2X 3 receptor subtypes are activated and inactivated within milliseconds (North and Suprenant, 2000), and may not be involved in the relatively slow Ca 21 signals measured in this study. In comparison, P2X 2 and P2X 4 receptors, like P2X 7 receptors, are able to form pores that dilate in the sustained presence of ATP (Khakh et al, 1999), and have been demonstrated on astrocytes (Ashour and Deuchars, 2004;Kukley et al, 2001;Zhao et al, 2006 nerves indicates that the main action of glutamate is to trigger the release of ATP through pore-forming P2X 7 receptors. That some cells did respond directly to glutamate when P2 receptors were blocked and in the P2X 2=2 7 nerve suggests that a subpopulation of glia respond to glutamate directly.…”
mentioning
confidence: 96%